ICCREM 2017. proceedings of the International Conference on Construction and Real Estate Management 2017, November 10-12 2017, Guangzhou, China - Wang, Yaowu; Pang, Yongshi; Shen, Qiping; Zhu, Yimin (College teacher) (American Society of Civil Engineers, 2017)
This collection contains 45 peer-reviewed papers on real estate and urbanization. Topics include: housing affordability; development site criteria and selection; and economics and real estate investment.
Keywords: Residential real estate -- Economic aspects -- China -- Congresses.; Housing -- Prices -- China -- Congresses.; Commercial real estate -- Economic aspects -- China -- Congresses.; City planning -- Technological innovations -- China -- Congresses.; Infrastructure (Economics) -- China -- Congresses.; elektronické knihy; electronic books